Effect of C677T Mutation in Methiylenetetrahydrofolate Reductase Gene and Blood Folate on Hypertension Risk - Mohammad Hakimi, Abdul Salam M Sofro, Sunarti Ahmad Husain Asdie (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2007)
Background: The prevalence of hypertension risk factor varies among race or ethnic groups. The varied prevalence is associated with culture or genetic differences or interaction between genetic and environment or nutrition factorsObjective: The aim of this study was to identify relationship between polymorphism of C677T in MTHFR gene and folate status towards the risk of hypertension among Javanese population.Methods: This study was case-control nested, in "Surveillance of Non-Communicable Diseases" in Purworejo, Central Java. The subjects were men with essential hypertension and 20-60 years old that had normal value of urine creatinine, blood glucose, cholesterol and triacylglycerol. They didnt take antihypertension drugs. The analysis of C677T polymorphism in MTHFR gene was done according to Frosst et al. (1995) method. The blood folate level was determined by Delfia-Folate Kit (PerkinElmer). The methods of Pfeiffer et al. (1999) was used to identify plasma total homocysteine level.Results: Odds ratio for subjects with CT genotype was 1.36 ICI: 95%:0.50;3.70); folate deficiency was 1.40 ICI: 95%:0.57;3.451; and both CT genotype and folate deficiency was 2.30 (CI: 95%:0.45;15.001. Homocysteine level of the cases with both folate deficiency and CT genotype was 45.28 .:!:. 30.39; and only folate deficiency was 17.94.:!:. 12.77; whereas in the control with both folate deficiency and CT genotype was 21.44.:!:. 10.71 and only folate deficiency was 11.79.:!:. 5.28.Conclusions: The effect of folate deficiency to homocysteine level and hypertension risk was slighly stronger than the genetic effect of C677T in MTHFR gene. In subjects with normal folate level, the CT genotype did not influence homocysteine level.Kata kunci:polymorphism, methylenetetrahydrofolate reductase, folate, hypertension